Project Report Offline Synchronization of XML Files - BANU PRAKASH, GAYATHRI S and HAMSA SHREE (2006)
INTERNAL GUIDE: SWARNALATHA R RAO, MVJCE EXTERNAL GUIDE: T B DINESH, SERVELOTS INFOTECH
Keywords: Offline Synchronization of XML Files